2022
DOI: 10.1039/d2sc02124b
|View full text |Cite
|
Sign up to set email alerts
|

Water as a monomer: synthesis of an aliphatic polyethersulfone from divinyl sulfone and water

Abstract: Using water as monomer in polymerization reactions presents a unique and exquisite strategy towards more sustainable chemistry. Herein, the feasibility thereof is demonstrated by the introduction of the oxa-Michael polyaddition...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In 2008, Ueda et al demonstrated that their polyether sulfone is characterized by a high refractive index of 1.686, a high Abbe number of 48.6, a glass transition of 152 °C, and high optical transparency (>99%) in the visible light range of 400 to 800 nm, which appears to be well-suited for optical lenses or related applications. 2,5,7,128 Sulfone moieties are mainly introduced by oxidation of sulfides, by Michael addition on corresponding vinyl sulfones, 139,140 or by direct radical copolymerization of vinyl monomers with SO 2 . [141][142][143] The latter was mainly used to create thermally degradable materials due to the thermal instability of the resulting C-S bond.…”
Section: Vinyl Sulfonesmentioning
confidence: 99%
“…In 2008, Ueda et al demonstrated that their polyether sulfone is characterized by a high refractive index of 1.686, a high Abbe number of 48.6, a glass transition of 152 °C, and high optical transparency (>99%) in the visible light range of 400 to 800 nm, which appears to be well-suited for optical lenses or related applications. 2,5,7,128 Sulfone moieties are mainly introduced by oxidation of sulfides, by Michael addition on corresponding vinyl sulfones, 139,140 or by direct radical copolymerization of vinyl monomers with SO 2 . [141][142][143] The latter was mainly used to create thermally degradable materials due to the thermal instability of the resulting C-S bond.…”
Section: Vinyl Sulfonesmentioning
confidence: 99%
“…The material was characterized as solid polymer electrolyte based on its high electrochemical stability, appealing conductivity, and solvent-free membrane preparation. [56] Scheme 5 Poly(ether-sulfone) derived from the oxa-Michael polymerization of water and divinyl sulfone.…”
Section: 1poly(ether-sulfone)smentioning
confidence: 99%
“…[32,69] The effect of the reaction temperature has also been studied numerous times. [43,52,56,70] Oxa-Michael polymerizations proceed nicely at room temperature and higher molar mass can be obtained compared to polymerizations at elevated temperatures. The worse performance at high temperatures results from side reactions, in specific from concurring vinyl addition reactions such as Rauhut-Currier reaction or anionic polymerization.…”
Section: Effects Of Solvent and Temperaturementioning
confidence: 99%
“…By using deuterated water, we also observed partial deuteration of the vinyl. 23 Examples for applying the retro oxa-Michael reaction include the evaporation of water from hydroxy ethyl sulfone derivatives at room temperature under basic conditions (pH = 8.5) to obtain reactive vinyl groups which can then further react with alcohols. 24 However, this is described to be a very slow process, taking several days.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, at 80 °C, 1,4-oxathiane 4,4-dioxide could be prepared selectively from bishydroxy ethyl sulfone under basic conditions within 24 h by the loss of water. 23 Moreover, methylene malonate derivatives can be blocked with Michael donors such as alcohols or thiols. By the reverse Michael reaction, the alkene is liberated upon heat treatment (>200 °C).…”
Section: Introductionmentioning
confidence: 99%